ANALISIS RISIKO KREDIT, RISIKO OPERASIONAL DAN PROFITABILITAS PERUSAHAAN SEBELUM DAN SESUDAH AKUISISI PADA PT. ALLO BANK INDONESIA TBK PERIODE 2018-2023 - Tia Mutiara Sari; Anis Feblin; Rr. Dimas Veronica Priharti (Ekonomika, 2025)
This study aims to examine the differences in credit risk, operational risk, and profitability before and after the acquisition of PT Allo Bank Indonesia Tbk during the 2018–2023 period. A quantitative approach was employed using secondary data, with a total of 24 observations analyzed. The data analysis methods used were the Wilcoxon Signed Rank Test and Paired t-Test, processed using SPSS version 20. The results reveal significant differences in credit risk (measured by Non-Performing Loan/NPL), operational risk (measured by the Operating Expense to Operating Income/BOPO ratio), and profitability (measured by Return on Assets/ROA) between the pre- and post-acquisition periods.